High-wettability brass flux-cored brazing filler metal and preparation method thereof
By adding Sn, Ni and its composite alloy powder to the brass flux core brazing material, it is solved, and the problems of non-degradability of cadmium and increased production costs in traditional brazing processes are achieved, and low melting temperature and high The brass flux core brazing material with tensile strength improves brazing efficiency and quality.
Patent Information
- Application Number
- CN202310812698.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
AI Technical Summary
The non-degradability of cadmium in existing silver-based brazing materials and the rising price of precious metal silver have led to an increase in production costs, and the separate use of solder and flux in traditional brazing processes affects the processing cycle and brazing quality.
Using highly wettable brass flux core solder, it is prepared into thin strip form by adding Sn, Ni and its composite alloy powder. The tubular structure is formed through rolling and rotary forging processes, reducing the melting speed of the flux core and improving welding. Tensile strength of seam.
The brass flux core brazing material has been achieved with low melting temperature, good wetting and high tensile strength, which improves brazing efficiency and quality, reduces production costs, and avoids the toxicity of cadmium.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brazing materials of metal materials, and in particular to a brass flux-cored brazing filler metal with high wettability and a preparation method thereof. Background Art
[0002] Silver-based solder has a moderate melting temperature (generally 600-790℃) and good gap-filling ability, and can obtain high-strength and high-reliability brazed joints. It has been widely used in aerospace, automobile manufacturing, household appliances, electric power, superhard tools and other fields. Among them, Ag-Cu-Zn-Cd solder has a lower melting temperature due to the addition of Cd, which expands the brazing range of the base material. At the same time, it is low in price, has good machinability, wetting and spreading properties, and mechanical properties of the brazed joint, and has always been popular in the manufacturing industries of household appliances, household appliance parts, electrical instruments, etc.
[0003] However, cadmium is a non-degradable toxic element that will accumulate in the human body and is harmful to human health. It cannot be recycled or rendered harmless and can only be banned.
[0004] However, due to the excessive use of non-renewable resources, the price of precious metal silver continues to rise, resulting in an increase in the production costs of manufacturers. In order to make a reasonable allocation of non-renewable resources and reduce manufacturing costs, people have paid attention to brass solder.
[0005] With the continuous emergence of new structures and new materials, the requirements for brazing technology are becoming higher and higher. During the brazing process, the mutual diffusion of elemental components between the base material and the brazing filler metal is achieved through the wetting effect of the brazing filler metal and the base material surface and the capillary action at the brazing seam. After cooling and solidification, microstructures such as solid solution, eutectic and intermetallic compounds are formed at the brazing seam and interface, achieving intercrystalline or intracrystalline metallurgical bonding between the base material and the brazing filler metal. The quality of the brazed joint depends to a large extent on the brazing filler metal. In traditional processes, the method of using brazing filler metal and brazing flux separately has always affected the processing cycle and brazing quality. The introduction of flux-cored brazing filler metal can change this situation.
[0006] Brass flux core has been widely used in brazing connections and has shown excellent performance. It is often used in brazing connections between steel and steel, and copper and steel. The use of brass flux core improves the operation mode of adding flux while brazing in the traditional process. The use of flux core brazing material can obtain brazed joints with good joint performance, smooth joint surface, high strength, and good mechanical properties. At the same time, the flux core brazing material can make the flux and the brazing material into one in a certain proportion, reduce the brazing temperature, improve the shortcomings of the traditional process of applying flux to limit the welding efficiency, greatly improve the brazing efficiency and brazing quality, and also reduce the melting point difference between the flux and the brazing material. Summary of the invention
[0007] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a brass flux core solder with high wettability and a preparation method thereof are provided. The brass flux core solder with Sn, Ni and Sn-Ni composite alloy powder added has good tensile resistance, a low melting temperature range and high wettability.
[0008] In order to achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] Further, 0wt.% Sn, 3wt.% Sn, 5wt.% Sn, 7wt.% Sn, 10wt.% Sn, 15wt.% Sn, and 20wt.% Sn powders were added to the brass core brazing flux powder respectively;
[0010] Further, 0wt.% Ni, 10wt.% Ni, 20wt.% Ni, 30wt.% Ni, 40wt.% Ni, and 50wt.% Ni powders were added to the brass core brazing flux powder respectively;
[0011] Further, 3wt.% Sn-0wt.% Ni, 0wt.% Sn-10wt.% Ni, and 3wt.% Sn-10wt.% Ni composite alloy powders were added to the brass core brazing flux powder respectively;
[0012] The above are all weight percentages of alloy powder in flux powder.
[0013] The above-mentioned preparation method of adding alloy powder to flux core brazing flux comprises the following steps:
[0014] (1) Step 1, selection and preparation of raw materials: brass flux-cored brazing filler metal is prepared by strip rolling method, the brass flux-cored brazing filler metal alloy is prepared into a thin strip, and then subjected to recrystallization annealing treatment and cleaning to remove impurities.
[0015] (2) Step 2, rolling and adding powder to the brass flux-cored solder alloy: The brass flux-cored solder alloy is deformed by the forming rolling mill and rolled into an upwardly open U-shaped groove. The dosing mode is set to the shock-powder interlocking mode. Different weight ratios of alloy powder are added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through the powder feeding device. By adjusting the conveying rate of the strip and the powder feeding rate of the solder, an optimal rate coordination is achieved to ensure that the solder filling rate is uniform, accurate and stable. After being deformed by roller rolling, it becomes an overlapping tubular structure (that is, the open ends of the U-shaped strip overlap to form a tubular solder), forming a flux-cored solder of the required specifications;
[0016] (3) Step 3: Rotary forging and reducing the diameter of the brass flux-cored solder: The speed of each roller is controlled by an electrical control system, and the flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is subjected to rotary forging, and this process is repeated multiple times to obtain a finished brass flux-cored solder.
[0017] Furthermore, after the brazing alloy is prepared in step (1), a cleaning process is also included. The cleaning process is to use acetone as a cleaning solvent and oscillate and clean the metal raw material in an ultrasonic wave for 20 minutes. The power density of the ultrasonic wave is 0.8 W / cm 2 , the frequency is 33Hz.
[0018] Furthermore, the thickness of the thin strip in step (1) is prepared to be 1.9-2.0 mm.
[0019] Furthermore, in step (3), the width of the overlapping portion L of the core solder is 0.05-0.3 mm; and the multiple times are 4 to 5 times.
[0020] Beneficial technical effects: The brass flux-cored solder with added Sn / Ni / Sn-Ni alloy powder of the present invention has an increased tensile strength, a decreased solidus-liquidus temperature, and an increased spreading area as the content of Sn / Ni / Sn-Ni alloy powder increases. Figures and Tables
[0021] Figure 1 .XRD result diagram of solder with -X% Sn added.
[0022] Figure 2 .Add -X% Sn solder melting temperature.
[0023] Figure 3 .Add -X% Sn solder spreading area.
[0024] Figure 4 .Add -X% Sn solder to improve weld hardness.
[0025] Figure 5 .Add -X% Sn solder tensile strength.
[0026] Figure 6 .Add -X% Ni solder metallography (200X).
[0027] Figure 7 .Add-X%Ni solder scan (1000X).
[0028] Figure 8 .XRD result diagram of solder with -X% Ni added.
[0029] Fig. 9 .Add -X% Ni solder melting temperature.
[0030] Fig.10 .Add -X% Ni solder spreading area.
[0031] Fig.11.Add -X% Ni solder to improve weld hardness.
[0032] Fig.12 .Add -X%Ni to improve the tensile strength of solder.
[0033] Fig.13 .Metallographic structure of composite Sn-Ni solder (200X).
[0034] Fig.14 .Scanning of composite Sn-Ni solder (1000X).
[0035] Fig.15 .Spreading performance of composite Sn-Ni solder.
[0036] Fig.16 .Energy spectrum point analysis results of solder with -X% Ni added. DETAILED DESCRIPTION
[0037] The implementation process of the present invention and the performance of the material are illustrated by examples:
[0038] The following are the weight percentages of alloy powder in the flux.
[0039] Example 1
[0040] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 0wt.% Sn powder to brass flux core brazing powder is provided. The preparation method of the brass cored solder is as follows:
[0041] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0042] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 0wt.% Sn powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. It is then deformed by a rolling roller to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0043] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0044] Example 2
[0045] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 3wt.% Sn powder to brass flux core brazing powder is provided.
[0046] The preparation method of the brass cored solder is as follows:
[0047] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0048] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 3 wt.% Sn powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. Then, it is deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0049] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0050] Example 3
[0051] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 5wt.% Sn powder to brass flux core brazing powder is provided.
[0052] The preparation method of the brass cored solder is as follows:
[0053] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0054] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 5 wt.% Sn powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. Then, it is deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0055] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0056] Example 4
[0057] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 7wt.% Sn powder to brass flux core brazing powder is provided.
[0058] The preparation method of the brass cored solder is as follows:
[0059] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0060] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 7% Sn powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. It is then deformed by a rolling roller to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0060] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0061] Example 5
[0062] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 10wt.% Sn powder to brass flux core brazing powder is provided.
[0063] The preparation method of the brass cored solder is as follows:
[0064] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0065] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 10 wt.% Sn powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. Then, it is deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0066] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0067] Example 6
[0068] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 15wt.% Sn powder to brass flux core brazing powder is provided.
[0069] The preparation method of the brass cored solder is as follows:
[0070] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0071] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 15 wt.% Sn powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. Then, it is deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0072] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0073] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 20wt.% Sn powder to brass flux core brazing powder is provided.
[0074] The preparation method of the brass cored solder is as follows:
[0075] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0076] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 20 wt.% Sn powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. Then, it is deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0077] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0078] Example 8
[0079] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 10wt.% Ni powder to brass flux core brazing powder is provided.
[0080] The preparation method of the brass cored solder is as follows:
[0081] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0082] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 10 wt.% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device, and then deformed by a rolling roller to form an overlapping tubular structure (i.e., the open ends of the U-shaped belts are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0083] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0084] Example 9
[0085] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 20wt.% Ni powder to brass flux core brazing powder is provided.
[0086] The preparation method of the brass cored solder is as follows:
[0087] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0088] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 20 wt.% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device. Then, it is deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0089] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0090] Example 10
[0091] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 30wt.% Ni powder to brass flux core brazing powder is provided.
[0092] The preparation method of the brass cored solder is as follows:
[0093] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0094] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 30 wt.% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device, and then deformed by a rolling roller to form an overlapping tubular structure (i.e., the open ends of the U-shaped strips are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0095] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0096] Embodiment 11
[0097] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 40wt.% Ni powder to brass flux core brazing powder is provided.
[0098] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0099] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 40 wt.% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device, and then deformed by a rolling roller to form an overlapping tubular structure (i.e., the open ends of the U-shaped belts are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0100] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0101] Example 12
[0102] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a method of adding 50wt.% Ni powder to brass flux core brazing powder is provided.
[0103] The preparation method of the brass cored solder is as follows:
[0104] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0105] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 50 wt.% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device, and then deformed by a rolling roller to form an overlapping tubular structure (i.e., the open ends of the U-shaped belts are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0106] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0107] Embodiment 13
[0108] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a composite powder of 3wt.% Sn-0wt.% Ni is added to the brass flux core brazing powder.
[0109] The preparation method of the brass cored solder is as follows:
[0110] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0111] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 3wt.% Sn-0wt.% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device, and then deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped belts are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0112] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0113] Embodiment 14
[0114] In order to reduce the melting speed of the flux core and improve the tensile strength of the weld, a composite powder of 0wt.% Sn-10wt.% Ni is added to brass flux core brazing powder.
[0115] The preparation method of the brass cored solder is as follows:
[0116] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0117] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 0wt.% Sn-10wt.% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device, and then deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped belts are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0118] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0119] Embodiment 15
[0120] In order to reduce the melting speed of flux core and improve the tensile strength of weld, a composite powder of 3% Sn-10% Ni is added to brass flux core brazing powder.
[0121] The preparation method of the brass cored solder is as follows:
[0122] (1) The brass flux-cored solder alloy is prepared into a thin strip with a thickness of 1.9-2.0 mm, subjected to a recrystallization annealing treatment, and cleaned to remove impurities.
[0123] (2) The brass flux-cored solder alloy is curled and deformed by a forming rolling mill and rolled into an upwardly open U-shaped groove. 3% Sn-10% Ni powder is added to the flux-cored solder powder. At the same time, the prepared flux core is continuously added to the U-shaped groove through a powder feeding device, and then deformed by roller rolling to form an overlapping tubular structure (i.e., the open ends of the U-shaped belts are overlapped to form a tubular solder), thereby forming a flux-cored solder of the required specifications.
[0124] (3) The width of the overlapped part L of the flux-cored solder is 0.05-0.3 mm. The speed of each roller is controlled by an electrical control system. The flux-cored solder passes through a brush wheel. The brass flux-cored solder after rolling and closing is rotary forged to obtain a finished brass flux-cored solder.
[0125] The above experimental examples were subjected to microscopic structural analysis and phase analysis (metallographic, scanning, XRD diagram), and solder performance tests (melting characteristic test, wettability test and weld joint mechanical property test).
[0126] Microscopic tissue analysis: Cut and inlay the rolled solder and interface of each component separately. Try to ensure that the intercepted parts are the same. Use a cutting machine to cut the sample to be observed into pieces with an area of about 1mm. 2Place the sample in the ZXQ-1 inlay machine, pour in an appropriate amount of inlay powder, set the inlay temperature at 130°C, and set the time for 20 minutes. After the inlay is completed, use a pre-grinder to process the sample, and then polish it on sandpaper No. 200, No. 400, No. 600, No. 800, and No. 1200 in turn until the scratches on the surface of the specimen are evenly spaced and in the same direction. Choose nylon polishing cloth and 1.5μm diamond polishing paste for polishing. During the polishing process, add clean water continuously to prevent excessive polishing of the surface due to friction heat. The polishing process is until no obvious scratches are observed under an optical microscope. Before observation, clean the sample with anhydrous ethanol, dry the surface moisture with a hair dryer, and then use the corrosion solution prepared by FeCl3 (5g) + HCl (50ml) + H2O (100ml) to corrode. Use a cotton swab dipped in the prepared corrosion solution to corrode and wipe the sample surface for 1-2s. Then rinse with deionized water, dry with a hair dryer, and use an MDS400 metallographic microscope for metallographic observation. If scratches still exist, repeat the above steps. The final metallographic sample can be analyzed by Leica DM6M optical microscope and SU8010 scanning electron microscope, and the distribution of elements and composition ratio of each phase can be analyzed by combining electric scanning, surface scanning and line scanning.
[0127] Phase analysis: The metal sample to be tested is fixed in a glass slide by plasticine and placed under the Cu-Kα target material. The test voltage is set to 40kV, the test current is 40mA, the scanning speed is 10° / min, and the detection angle range is 0°~90°. The obtained XRD data is analyzed using Jade 6 software, and the phase of the tested material is finally determined and reasonably marked by comparing with the PDF card of the standard material, which is convenient for comparison and observation.
[0128] Examples 1-7 respectively add 0wt.% Sn, 3wt.% Sn, 5wt.% Sn, 7wt.% Sn, 10wt.% Sn, 15wt.% Sn, 20wt.% Sn powder to the brass core flux powder. Figure 1 As shown in the figure, the magnification is 200X. It can be seen that when no alloy powder is added, the flux-cored solder matrix microstructure is mainly composed of gray-black coarse dendritic α copper and light-colored (α+β) dual-phase structure between dendrites. With the increase of Sn element content, the proportion of α phase in the microstructure gradually decreases, and the α phase precipitated in the (α+β) dual-phase structure also decreases, gradually developing into β phase block grains. A small amount of fine dendritic α phase is arranged in a large angle orientation at the block β phase grain boundary.
[0129] The metallographic images of Examples 8-12, where 10wt.%Ni, 20wt.%Ni, 30wt.%Ni, 40wt.%Ni and 50wt.%Ni powders are added to the brass flux core solder, are shown in FIG. Figure 6As shown, the magnification is 200X, and the scanning images of brass flux core solder of Examples 8-12 are as follows Figure 7 As shown, the magnification is 1000X, and the XRD results of brass flux core solder of Examples 8-12 are as follows Figure 8 As shown, the diffraction analysis results of brass cored solders of Examples 8-12 are as follows Fig.16 As shown in the figure, it can be seen that when no alloy powder is added, the α phase of the flux core solder matrix microstructure is in the form of elongated strips, arranged alternately with the β phase; after adding 10wt.% Ni, the α phase is more developed, the length is significantly shortened, and the width is wider. This is because, on the one hand, Ni is infinitely miscible with Cu, and the solubility of Zn in the CuNi solid solution is greater than that in the Cu solid solution. The addition of Ni expands the α phase region and increases the proportion of the α phase. On the other hand, due to its high melting point, Ni atoms are easily precipitated in advance during the solidification process to form a large number of heterogeneous nuclei, which is beneficial to the refinement of the grain size; when the addition amount of Ni is 20wt.%, the organizational morphology changes significantly, with small, uniform equiaxed crystals as the main component, and the number of β phases distributed between the α phases is significantly reduced, and they are distributed in the form of islands, separated by α phases, and there is also a segregation phenomenon.
[0130] Examples 13-15 respectively add 3wt.% Sn-0wt.% Ni, 0wt.% Sn-10wt.% Ni, and 3wt.% Sn-10wt.% Ni composite alloy powders to the brass flux core solder. Fig.13 As shown, the magnification is 200X, and the scanning images of the brass flux core solder of Examples 13-15 are as follows Fig.14 As shown in the figure, the magnification is 1000X. It can be seen that after adding 3Sn-10Ni composite alloy powder, the microstructure of the flux-cored solder matrix is mainly composed of blocky α and thin strip β. The α phase is transformed from slender and disordered dendrites to large and short equiaxed crystals with obvious orientation arrangement. Compared with the flux-cored solder with only Sn powder added, the proportion of α phase in the organization increases and the proportion of β phase decreases. Compared with the solder organization with only Ni powder added, the α phase is evenly distributed and equal in size. The two-phase organization exists between the α phases, and the irregular intercrystalline organization is changed into a slender interdendritic organization.
[0131] Melting characteristic test: The solder melting temperature test is carried out using a STA404 F3 synchronous thermal analyzer. 5-15 mg of the solder to be tested is placed in a platinum crucible, argon is selected as the protective atmosphere, the temperature range is set to 200°C to 1000°C, and the heating rate is 10°C / min. The measured solder DSC (Differential Scanning Calorimeter) curve is based on the national standard GB / T 1425-2021 Thermal analysis experimental method for the determination of the melting temperature range of precious metals and their alloys. The DSC data is analyzed, its solid-liquid phase line is calibrated, and the melting temperature range is determined.
[0132] The melting temperature of the brass flux core solder of Examples 1-7 varies as follows: Figure 2 As shown in the figure, it can be seen that with the increase of Sn element content, the solid-liquid phase line gradually decreases, especially in the range of 7wt.% Sn, the downward trend is obvious. Since the solid phase line decreases faster than the liquid phase line, the melting temperature range gradually increases.
[0133] The melting temperature of the brass cored solder of Examples 8-12 varies as follows: Fig. 9 As shown, it can be seen that with the increase of Ni element content, the melting temperature range gradually decreases, the viscosity decreases, the fluidity increases, and the speed at which the solder changes from a solidified state to a molten state is accelerated.
[0134] Wettability test: The wettability test of the test solder was carried out in accordance with the national standard GB / T 11363-2008 "Test Method for Wettability of Solder". In this experiment, Q235 steel plate was used as the spreading base material. In order to ensure that the surface of the sample was clean and flat, it was first polished with 600 silicon carbide sandpaper before the test. The pre-ground base material was ultrasonically cleaned with alcohol and then placed in a drying oven for use. Weigh 20 mg of solder samples containing different Sn, Ni and Sn-Ni composite alloy powders and place them in the center of the treated base material. When the spreading furnace reaches the preset temperature, put in the solder. When the solder melts, keep it warm for 30 seconds, take out the steel plate and quickly put it in cold water for cooling, wash off the excess solder on the surface of the base material, take photos of the samples with a digital camera, and import them into AutoCAD to calculate the spreading area of the solder. Each sample was tested 3-5 times to take the average value.
[0135] The spreading area of the brass flux cored solder of Examples 1-7 varies as follows: Figure 3 As shown in Figure 2, it can be seen that with the addition of Sn content, the unit spreading area of brass flux core solder increases. When the Sn addition amount is 20wt.%, the unit spreading area reaches a maximum value of 4.22mg / mm 2 This is because Sn powder can also melt into liquid at a lower temperature. The addition of Sn element can reduce the melting temperature of brass flux-cored solder, thereby reducing the viscosity of liquid metal, enhancing the fluidity of liquid metal, and ultimately improving the wetting and spreading performance of solder.
[0136] The spreading area of the brass cored solder of Examples 8-12 varies as follows: Fig.10 As shown in the figure, it can be seen that with the increase of Ni content, the spreading area shows a trend of first increasing and then decreasing. When the Ni content is 20wt.%, the spreading area is the largest, which is 2.46mg / mm 2, an increase of 66.2%. This is because Ni can form a continuous solid solution with Cu and Fe, reducing surface tension. At the same time, adding Ni can increase the melting temperature. The superheat of the viscous fluid at the same wetting temperature is reduced, the viscosity is increased, and the wetting performance is deteriorated. In addition, the Ni content is too high and the flux content is low, which cannot remove the oxide film well and reduces the wetting performance.
[0137] The spreading area of brass flux core solder of Examples 13-15 varies as follows: Fig.15 As shown, it can be seen that the unit spreading area of 3wt.% Sn-10wt.% Ni is the largest, that is, the wettability is the largest. Since the addition of Sn can increase the flowability, Ni can form a continuous solid solution with Cu and Fe to reduce the surface tension.
[0138] Mechanical properties test method: The brazing experiments in this article all adopt the butt welding method. Use oxygen-acetylene flame to weld the Q235 steel plate base material. The steel plate sample size is 50mm×10mm×1mm, the acetylene flow rate is 1.4L / min, and the oxygen is 0.9L / min. Before brazing, check whether the base material joint is aligned, flat, and smooth to avoid bending of the sample after welding, which will affect the experimental data. The butt joint of the sample cannot be completely close, leaving 1mm 2 Gap, easy for the brazing material to flow in. Use sandpaper to grind the side of the parent material to be welded, clean it with ethanol, and dry it in an oven for later use. After welding is completed, use a grinder to grind off the excess brazing material at the brazed joint to make the weld thickness consistent with the parent material. The mechanical properties test of the brazed joint is carried out in accordance with the national standard GB / T 11363-2008 "Brazed Joint Strength Test Method". The mechanical properties of the brazed joint are tested using a SANS-CMT5105 universal tensile testing machine, and the test loading rate is 2mm. 2 / min. The hardness test was carried out in accordance with the provisions of GB / T27552-2011 "Destructive test of welds of metal materials - Microhardness test of welded joints". To ensure the accuracy of the test results, the performance data of the embodiments and comparative examples are the average values of three identical samples.
[0139] Example 1-7 Brass flux cored brazing filler metal weld hardness changes as follows Figure 4 As shown, the tensile strength of brazed joints in Examples 1-7 varies as follows Figure 5As shown in the figure, with the addition of Sn powder content, the weld hardness increases slowly, and the tensile strength of the brazed joint increases first, then decreases, then increases, and then decreases. When the Sn powder addition amount is 3%, the brazed joint strength reaches a maximum value of about 324 MPa. When Sn powder is not added to the flux core powder, the brazing seam structure mainly contains large blocks of Cu-based solid solution mainly composed of CuZn phase, and the tensile strength of the brazed joint is not high. With the increase of Sn powder content, the Ag-Cu eutectic in the joint structure increases after adding 3% Sn, so the joint strength increases. However, with the continued addition of Sn powder, the eutectic component in the brazing seam decreases, and the columnar (Cu) size decreases, so the joint strength decreases. With the continued addition of Sn powder, the Ag-Cu eutectic structure in the joint almost disappears, the structure is significantly coarsened, and a large number of CuSn and CuZn brittle compounds appear at the same time. The adsorption of low-melting-point metal Sn atoms reduces the shear bonding force between the atoms of the metal material, thereby promoting the nucleation and slip of dislocations at and near the crack tip. Under the action of external stress, stress concentration is easily generated around the hard and brittle compounds and coarse structures in the brazed joint structure, making it difficult to achieve coordinated and synchronous deformation with the brazing material matrix, resulting in the initiation of cracks, which increases the local plasticity at the crack tip. The increase in local plasticity can reduce the overall fracture strain of the brazed joint, making the joint brittle, so the joint strength will decrease.
[0140] Example 8-12 Brass flux cored brazing filler metal weld hardness changes as follows Fig.11 As shown, the tensile strength of brazed joints in Examples 8-12 varies as follows: Fig.12 As shown, it can be seen that with the increase of Ni content, the hardness first decreases and then increases, and the tensile strength first increases and then decreases. This is because with the increase of Ni content, the α phase gradually increases and the β phase decreases, so that Sn with extremely low solid solubility in α is enriched at the boundary. The more Ni, the more obvious the segregation of Sn element. The atomic radius of Sn is larger than that of Cu, which increases the degree of organizational distortion or defect density at the boundary and increases the hardness.
[0141] The brass flux cored brazing material prepared by the present invention has an increased area and quantity of α phase and a decreased β phase as the content of Sn / Ni / Sn-Ni alloy powder in the flux cored brazing powder increases, resulting in a decreased melting speed of the brazing alloy, an increased tensile strength, an increased spreading area, and increased wettability. After adding 3wt.% Sn-10wt.% Ni, the brass flux cored brazing material has high wetting and spreading performance and tensile resistance, and a reduced melting temperature range, thereby improving brazing efficiency and brazing quality and improving brazing technology. The preparation method of the present invention is simple and reliable, the selected elements are non-toxic and easy to obtain, the economy is good, the alloy performance is good, and the application value is high.
Claims
1. A method for preparing a brass cored solder with high wettability, characterized in that: Further, Sn powder in different weight ratios was added to the brass flux core solder; Further, different weight ratios of Ni powder were added to the brass flux core brazing filler metal; Further, adding Sn-Ni composite metal powder in different weight ratios to the brass flux core brazing filler metal; The above weight ratios are all weight percentages of alloy powder in the flux.
2. The method for preparing a brass core by adding Sn powder in different weight ratios according to claim 1, characterized in that: The Sn powders with different weight ratios are 0wt.% Sn, 3wt.% Sn, 5wt.% Sn, 7wt.% Sn, 10wt.% Sn, 15wt.% Sn, and 20wt.% Sn powders respectively.
3. The method for preparing brass core by adding Ni powder in different weight ratios according to claim 1, characterized in that: The Ni powders with different weight ratios are 0wt.% Ni, 10wt.% Ni, 20wt.% Ni, 30wt.% Ni, 40wt.% Ni, and 50wt.% Ni powders.
4. The method for preparing a brass core by adding Sn-Ni composite metal powders in different weight ratios according to claim 1, characterized in that: The Sn-Ni composite metal powders with different weight ratios are 3wt.% Sn-0wt.% Ni, 0wt.% Sn-10wt.% Ni, and 3wt.% Sn-10wt.% Ni composite metal powders respectively.
5. The method for preparing a brass core by adding Sn-Ni composite metal powders in different weight ratios according to claim 4, characterized in that: The optimal ratio of adding Sn-Ni composite powder is 3wt.% Sn-10wt.% Sn.
6. The brass flux-cored solder with high wettability according to claim 1, characterized in that: The purity of the metal raw material is greater than 99.9 wt %.
Citation Information
Cited By
Double-ring air injection system for improving spreadability of CMT repair welding cast aluminum alloy and repair welding method
CN121847906A